He Can algorithms have a synergistic relationship with neoliberalism? Essay on control societies and governmentality. - Vich, Juan José (2024)
This paper seeks to analyse the relationship between neoliberal governmentality and algorithmic governmentality. From the theoretical characterization of the different phenomena that compose them, our hypothesis states that there is a synergic relationship between both governmentalities. The notion of governmentality speaks about the way in which we are governed and govern ourselves. Neoliberalism seeks to establish itself as a rationality, while it establishes competition as the norm and enterprise as the mode of subjectivation. To this end, it draws on governmental techniques for the optimization of the individual. These techniques are amplified by machinic algorithms that are capable of collecting and processing data that are then used for profiling.